Surface structure determination by x-ray standing waves at a free-electron laser. (28th March 2019) - Mercurio, G; Makhotkin, I A; Milov, I; Kim, Y Y; Zaluzhnyy, I A; Dziarzhytski, S; Wenthaus, L; Vartanyants, I A; Wurth, W
Abstract: We demonstrate the structural sensitivity and accuracy of the x-ray standing wave technique at a high repetition rate free-electron laser, FLASH at DESY in Hamburg, by measuring the photoelectron yield from the surface SiO2 of Mo/Si multilayers. These experiments open up the possibility to obtain unprecedented structural information of adsorbate and surface atoms with picometer spatial and femtosecond temporal resolution. This technique will substantially contribute to a fundamental understanding of chemical reactions at catalytic surfaces and the structural dynamics of superconductors.